115k views
0 votes
(5x^a)(bx^2)=35x^8
a=
b=

User Misaki
by
5.0k points

1 Answer

5 votes

Answer:


a=6


b=7.

Explanation:

The given exponential equation is;


(5x^a)(bx^2)=35x^8

We multiply out to obtain;


5b(x^a)(x^2)=35x^8

Recall and use
a^m* a^n=a^(m+n)


5bx^(a+2)=35x^8

For the RHS to equal to the LHS,then


5b=35 and
a+2=8.


b=(35)/(5) and
a=8-2


b=7 and
a=6.

User Divyam Shukla
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.